Analisis Pendapatan, Willingness To Pay, dan Faktor Penentu Adopsi Benih Bersertifikat Petani Cabai Merah (Studi Kasus Kecamatan X-Koto, Kabupaten Tanah Datar) - Sarki, Yolanda; Novianti, Tanti; Wahyu Nugraheni, Sri Retno; Hardjanto, Arini (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2022)
One of the sectors in Indonesia's GDP that has an important role in increasing economic growth is the agricultural sector. The horticulture sub-sector ranked fourth and contributes 14,96 percenet to the GRDP of the agricultural sector in 2021. Red chili is one of the horticultural commodities that has market opportunities quite good in terms of price and expected to increase farmer’s income. One way to increase farmer’s income is to increase productivity, which is supported by superior or certificate seed varieties. The objective of this study are to analyze the factors that influence farmers to choose certified and non-certified seeds, analyze the factors that influence the income of red chili farmers and the willingness to pay for red chili farmers to use certified and non-certified seeds in X-Koto District, Tanah Datar Regency. The method used in this study are binary logistic analysis, multiple regression analysis, and contingent valuation method. Based on the results of the study, the variables that significantly influenced farmers to choose certified seeds were age, education, land area, family responsibilities, farming experience, and acceptance. Factors that affect the income of farmers who use certified seeds are land area and education, while farmers who use non-certified seeds are land area and revenue. This showed that farmer’s education greatly influences their willingness to accept new innovations including the use of certified seeds in farming The farmer’s average willingness to pay for certified and non-certified red chili seeds is Rp31.165/10 gram and Rp67.331/10 gram.